2022
DOI: 10.3389/fcimb.2022.1000291
|View full text |Cite|
|
Sign up to set email alerts
|

Zonulin, a marker of gut permeability, is associated with mortality in a cohort of hospitalised peruvian COVID-19 patients

Abstract: Zonulin has previously been related to intestinal permeability in various inflammatory diseases, and more recently to the physiopathology of severe COVID-19 infections. We analysed serum samples from a previous study of a Peruvian cohort of hospitalised COVID-19 patients, for the quantification of zonulin by sandwich ELISA. Comparisons with clinical data, haematological and biochemical parameters and cytokine/chemokine levels were made. We found higher baseline zonulin levels in deceased patients, and zonulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…Zonulin is released in plasma after intestinal barrier disruption and is also considered a diagnostic marker of intestinal dysbiosis. 43 Our finding of elevated plasma zonulin in statins users supports these reports because statins can induce dysbiosis of intestinal microbes in experimental animal models. 44 Interestingly, a mechanistic relation between statins and intestinal barrier dysfunction has also been reported because atorvastatin reduces the expression of tight junction proteins in colonic epithelial cells.…”
Section: Discussionsupporting
confidence: 85%
“…Zonulin is released in plasma after intestinal barrier disruption and is also considered a diagnostic marker of intestinal dysbiosis. 43 Our finding of elevated plasma zonulin in statins users supports these reports because statins can induce dysbiosis of intestinal microbes in experimental animal models. 44 Interestingly, a mechanistic relation between statins and intestinal barrier dysfunction has also been reported because atorvastatin reduces the expression of tight junction proteins in colonic epithelial cells.…”
Section: Discussionsupporting
confidence: 85%
“…The dysbiosis of gut microbiota directly contributes to increased gut permeability, thereby facilitating the translocation of pathogenic bacteria and allowing the translocation of bacterial products from the gut into circulation ( Chen et al., 2022 ). Zonulin, LBP and sCD14 have been identified as reliable indicators of gut permeability and bacterial translocation ( Kavanagh et al., 2019 ; Palomino-Kobayashi et al., 2022 ). The Zonulin can be detected in plasma and exhibit a strong correlation with bacterial DNAemia, making it a valuable biomarker for assessing impaired gut barrier function ( Veres-Szekely et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SARS-CoV-2 spike stimulates the expression of zonulin, leading to the increase of gut permeability ( Llorens et al, 2021 ). Moreover, it was found that levels of zonulin in patients dying of severe COVID-19 are higher than those in patients recovered from the disease ( Giron et al, 2021 ; Palomino-Kobayashi et al, 2022 ). These data suggest that zonulin might be associated with poor outcomes in COVID-19.…”
Section: Long-term Gi Effects Of Long-covidmentioning
confidence: 99%